Microstructure, Mechanical, and Biological Properties of Porous Poly(vinylidene fluoride) Scaffolds Fabricated by Selective Laser Sintering - Wei Huang; Pei Feng; Chengde Gao; Xiong Shuai; Tao Xiao; Cijun Shuai; Shuping Peng (International Journal of Polymer Science)
Porous poly(vinylidene fluoride) (PVDF) scaffolds were prepared by selective laser sintering. The effects of laser energy density, ranging from 0.66 to 2.16 J/mm2, on microstructure and mechanical properties were investigated. At low energy density levels, PVDF particles could fuse well and the structure becomes dense with the increase of the energy density. Smoke and defects (such as holes) were observed when the energy density increased above 1.56 J/mm2 which indicated decomposition of the PVDF powder. The scaffolds appeared to be light yellow and there was a reduction in tensile strength. The fabricated scaffolds were immersed into simulated body fluid for different time to evaluate biostability. In addition, MG63 cells were seeded and cultured for different days on the scaffolds. The testing results showed that the cells grew and spread well, indicating that PVDF scaffolds had good biocompatibility.